The Influence of Leadership, Organizational Culture, and Work Environment on Employee Job Satisfaction(Case Study at Badan Pendapatan Daerah Kota Bekasi) - Sinta Dewi; Anita Novialumi (Indo Publishing, 2026)
This study aims to analyze the influence of leadership, organizational culture, and work environment on employee job satisfaction at the Bekasi City Regional Revenue Agency. The study used a quantitative method with a pre-survey approach. The study population was 87 employees and the entire population was sampled using a saturated sampling technique (census). Data collection was carried out through questionnaires and analyzed using validity tests, reliability, classical assumptions, multiple linear regression, t-test, F-test, and coefficient of determination (R²) with the help of SPSS version 27. The results showed that leadership had a positive but insignificant effect on job satisfaction with a calculated t value of 0.933 and a significance of 0.354. Organizational culture had a positive and significant effect on job satisfaction with a calculated t value of 4.191 and a significance of 0.000. The work environment also had a positive and significant effect on job satisfaction with a calculated t value of 5.895 and a significance of 0.000, and was the most dominant variable. Simultaneously, leadership, organizational culture, and work environment have a significant effect on job satisfaction with a calculated F value of 106.353 and a significance of 0.000. The coefficient of determination (R²) value of 0.794 indicates that 79.4% of job satisfaction can be explained by these three variables.